Case report: Successful experience using continuous infusion of meropenem in a geriatric patient with hip fracture complicated by sepsis - Kadralinova, Assiya; Bekniyazova, Assema Zh.; Konkayeva, Maiya E.; Yeltayeva, Aigerim A.; Konkayev, Aidos K. (Frontiers in Medicine, 2023)
This article highlights a clinical case of successful treatment of a 79-year-old multimorbid patient with a hip fracture resulting from a household injury. On the first day, the patient's injury was complicated by infection and pneumonia. As a result, arterial hypotension, tachysystole and respiratory failure progressed. With manifestations of sepsis, the patient was transferred to the intensive care unit. Surgical treatment in such situation was contraindicated due to the high operational and anesthesiological risks, unstable severe condition of the patient, as well as the presence of concomitant pathology in the form of coronary heart disease, obesity and schizophrenia. According to the new sepsis management guideline, it was decided to use a continuous 24-hour infusion of meropenem in addition to complex treatment of sepsis. The use of meropenem continuous infusion in this clinical situation may have caused the patient's clinical improvement, which increased her quality of life and decreased length of ICU stay and total hospital stay, despite an unfavorable cumulative prognosis and a high risk of in-hospital mortality.